GAMBARAN PENGETAHUAN GIZI IBU RUMAH TANGGA DAN STATUS GIZI BALITA DI DESA ILOHUNGAYO KECAMATAN BATUDAA KABUPATEN GORONTALO - Domili, Indra; Ntau, Liean N.; Ahmad, Sri Cindra (JOURNAL HEALTH AND NUTRITIONS, 2016)
ABSTRACT Knowledge of nutrition is all forms of information about food substances including the sources and functions needed for the body and its application in daily life. Knowledge of nutrition of housewives plays an important role in terms of improving nutrition at the family level, sorting out food, processing and serving menus at the household level is very much needed to improve nutrition at the family level. Mothers play a very important role in children's eating patterns. In regulating diet must be done regularly and thoroughly. The purpose of this study is to describe the knowledge of mothers about nutrition and describe the nutritional status of children in the village of Ilohungayo, Batudaa District, Gorontalo District. The population in this study were all children under five (age 0 59 months) in Ilohungayo Village as many as 37 people and respondents were mothers of children under five in the village of Ilohungayo. Toddlers status is calculated based on indicators of body weight according to WHO Antro with categories